PENGARUH TINGKAT KEBERLANJUTAN SERTA REPUTASI KAP TERHADAP PERINGKAT KREDIT PERUSAHAAN - Michael, Michael; Djajadikerta, Hamfri (Jurnal Akuntansi Kontemporer, 2021)
Research Purposes.  This study aims to determine the impact of the level of sustainability and reputation of KAP that can affect the assessment results of the credit rating process carried out by PEFINDO.Research Methods. In this study, the ordinal logistic regression analysis model is used to determine the probability of obtaining a credit rating for a company. Financial variable is described through level of sustainability prediction as calculated by using the value of the Altman Z-Score, while non-financial variable is described through the reputation of the KAP. There were 25 samples of companies that obtained credit ratings in a row from 2014 to 2018 by PEFINDO tested in this study.Research Result and Findings. The results of this study state that the level of sustainability prediction has a positive effect; whilst KAP reputation, which are not affiliated with Big 4, has a negative effect on the results of companies' credit ratings